Mechanisms of alveolar protein clearance in isolated rabbit lungs : role of clathrin- and caveolae-mediated endocytosis of albumin by the alveolar epithelium - Rummel, Sebastian; Justus Liebig University Giessen (My University, 2007)
Die Entstehung einer proteinreiche Ödemflüssigkeit in den Alveolen ist eine Hauptkomponente im Rahmen der Erkrankung Acute Lung Injury/Acute Respiratory Distress Syndrome (ALI/ARDS), welche zu einer massiven Einschränkung des Gasaustausches führt. Der onkotische Druck im Alveolus steigt massiv an, hält vermehrt Wasser in den Alveolen zurück und die Situation verschlimmert sich weiter. Die Auflösung des Ödems und die Verminderung der Proteinkonzentration sind also wichtigste Punkte für das Überleben des Patienten, wobei die Mechanismen zur Senkung der Albuminkonzentration in den Alveolen nicht vollständig bekannt sind. In dieser Arbeit wurden die Prozesse der Albumin-Clearence aus dem alveolaren Raum in das Gefäßsystem unter Zuhilfenahme des Modells der isolierten, ventilierten und perfundierten Kaninchenlunge untersucht. Zusätzliche Experimente in humanen epithelialen A549 Zellen wurden parallel durchgeführt, um die besondere Rolle des alveolaren Epithels beim Albumintransport näher zu beleuchten. Durch Vernebelung wurde 125I-Albumin in die isolierten Lungen eingebracht und der Transport dieses Proteins von der alveolaren auf die vaskulare Seite mittels Gamma-Detektoren in Echtzeit gemessen, wobei diese sowohl um die Lunge (Abnahme der Counts während des 120 min dauernden Versuches) als auch um das Perfusat (Zunahme der Counts) platziert worden sind. In Kontrollexperimenten (37°C) wurden in 120 Minuten 29,8 ± 2,2% des eingebrachten 125I-Albumin aus der Lunge in das Perfusate transportiert. Bei 4°C (3,7 ± 0,4%) oder 22°C (16,2 ± 1,1%) Lungentemperatur verminderte sich diese Transportrate signifikant. Daraus folgerten wir, dass dieser Prozess aktiv stattfand, wobei keine veränderten passiven, parazellularen Vorgänge bei verschiedenen Temperaturen beobachtet wurden. Dieser Transportprozess war sättigbar und uni-direktional, da in die Alveolen eingebrachtes, 1000fach stärker konzentriertes natives Albumin, den Transport von 125I-Albumin ins Perfusate signifikant verminderte. Dagegen hatte die Administration von nativem Albumin in das Perfusat keine Wirkung auf die Transportrate. Die Aufnahme von 125I-Albumin in A549 Zellen wurde massiv eingeschränkt, wenn kompetitiv natives Albumin beigegeben wurde, was gleichfalls die Theorie einer rezeptorvermittelten Aufnahme des Proteins stützt. Die Transportrate von 125I-Albumin in der Lunge verminderte sich signifikant, wenn Transzytose Inhibitoren (Phalloidin oleate oder Monensin) durch Vernebelung eingebracht wurden. Daraus folgte, dass 125I-Albumin wahrscheinlich mittels Transcytose in intaktem Zustand durch das Epithel geschleust wird, da Messungen aus brochoalveolaren Lavagen die Unversehrtheit von 125I-Albumin ergaben und vernebelte Protease Inhibitoren keine Änderungen der Transportrate zufolge hatten. Ausgangspunkt jeder Transzytose ist entweder Clathrin- oder Caveolae-vermittelte Endozytose. Um deren Beteiligung zu eruieren, vernebelten wir Inhibitoren der Clathrin-vermittelten Endozytose (Chlorpromazine oder Phenylarsine oxide) in die Alveolen, was zu einer signifikanten Verminderung der Transportrate von 125I-Albumin führte. Auch in den Zellen (monolayer) führte die Gabe dieser Substanzen zu deutlich geringeren Aufnahmeraten von Albumin. Administration von Inhibitoren der Caveolae-vermittelten Endozytose (NEM oder Filipin) ins Gefäßsystem führte ebenfalls zu erniedrigten Transportraten vom alveolaren Teil in das Perfusat. Die Verabreichung dieser Inhibitoren zu A549 Zellen war ebenfalls mit einem Rückgang in der Aufnahmerate von 125I-Albumin vergesellschaftet. Darüber hinaus führte die Kombination von Inhibitoren unterschiedlicher Endozytosetypen in A549 Zellen sogar zu noch geringeren Aufnahmeraten von 125I-Albumin in die Zellen, so dass wahrscheinlich beide Typen der Endozytose für den Transport von Albumin durch die alveolo-kapillare Barriere vonnöten sind. Diese Daten zeigen, dass der Transport von Albumin von der alveolaren Seite in das Gefäßsystem aktiv mittels Transzytose von statten geht. Beide Subtypen der Endozytose sind in diesen Prozess involviert. Ein weiteres Verstehen dieser Vorgänge ist von hoher klinischer Relevanz, da das Unvermögen einer adäquaten Protein-Clearence bei Patienten mit ALI/ARDS eng mit den Überlebenschancen dieser Erkrankung zusammenhängt.

A hallmark of acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is the accumulation of protein-rich edema fluid in the distal airspaces, leading to a life-threatening impairment of alveolar gas exchange. Accumulation of serum proteins (such as albumin) in the alveolar space leads to an increased oncotic pressure, thereby preventing fluid reabsorption and resulting in worse outcome. Thus, excess alveolar protein must be cleared for patients with ALI/ARDS to survive. However, the mechanism by which protein is removed from the alveolar space is not fully understood. To investigate the mechanisms of protein transport across the alveolo-capillary barrier, an isolated, ventilated and perfused rabbit lung model was employed. Additional experiments in human epithelial A549 cells were conducted to further evaluate the role of the alveolar epithelium in the transport of albumin. Radio-labeled albumin (125I-albumin) was deposited into the distal air spaces of isolated, ventilated and perfused rabbit lungs by ultrasonic nebulization, and clearance of 125I-albumin from the alveolar space was measured in real-time by gamma detectors placed around the lungs and around the perfusate reservoir. Under control conditions 29.8 ± 2.2 % of the radio-labeled alveolar albumin was transported (in 120 minutes) to the vascular compartment. Experiments conducted at 4 °C or 22 °C resulted in significantly lower albumin clearance (3.7 ± 0.4 or 16.2 ± 1.1 %, respectively), suggesting that the transport of albumin was facilitated by an active process (no changes in paracellular transport rates were observed). The transport of albumin across the alveolo-capillary barrier was saturable and uni-directional, since deposition of a 1000-fold molar excess of unlabeled albumin into the alveolar space prior to nebulization of 125I-albumin largely inhibited the transport of 125I-albumin to the vasculature, while administration of unlabeled albumin to the vascular space had no effect on albumin clearance. In line with these findings, administration of a 1000-fold molar excess of unlabeled albumin to A549 cells inhibited uptake of 125I-albumin, suggesting that albumin uptake by the alveolar epithelium was receptor-mediated. When lungs were treated with the transcytosis inhibitor monensin or the actin stabilizer phalloidin oleate, transit of albumin was significantly inhibited. No degradation of protein occurred in the alveolar space, as assessed by measurements of intact albumin from broncho-alveolar lavage samples; and pre-application of protease inhibitors, which had no effect on albumin clearance. These data collectively suggested that intact 125I-albumin was transcytosed by the alveolar epithelium. The initial step of transcytosis is either clathrin-dependent or caveolae-mediated. To further dissect the mechanism of albumin uptake by the alveolar epithelium, lungs were pretreated with the clathrin-dependent endocytosis inhibitors chlorpromazine or phenylarsine oxide. Inhibition of clathrin-dependent endocytosis resulted in a significant decrease in the albumin transport rate in intact lungs. Furthermore, administration of these inhibitors to A549 cells also decreased 125I-albumin uptake by these cells, confirming that clathrin-dependent endocytosis was important for albumin clearance from the alveolar compartment. Interestingly, administration of the caveolae-mediated endocytosis inhibitors, N-ethylmaleimide or filipin to the isolated lungs also resulted in a significant decrease in albumin clearance from the distal air spaces. Application of caveolae-mediated endocytosis inhibitors to A549 cells resulted in a similar decrease in 125I-albumin uptake. Moreover, co-administration of the clathrin and caveolae inhibitors had an additive effect, suggesting that both endocytic pathways were required for albumin uptake by the alveolar epithelium. Our data indicate that clearance of albumin from the distal air spaces is facilitated by active transcytosis across the alveolar epithelium of intact rabbit lungs. Both, clathrin- and caveolae-mediated endocytosis may play a role albumin transport from the alveolar compartment to the vascular space. Further understanding of these mechanisms is of clinical importance, since an inability to clear excess protein from the alveolar space is associated with poor outcome in patients with ALI/ARDS. Interfering with the protein clearance mechanisms at play in the lung may ultimately lead to novel therapeutic approaches for the treatment of this disease.
Keywords: ddc:630